CLUNK PHENOMENA ANALYSIS OF AUTOMOBILE TRANSMISSION SYSTEM BASED ON TORQUE ABRUPT CONDITION - ZHANG ZhiGang; PENG YuanPing; YU XiaoXia; ZHANG Yun (Jixie qiangdu)
Through the analysis of the transmission mechanism of the vehicle transmission system,the torsional vibration model of the 12-DOF multi-gap nonlinear powertrain system was established,and the transient shock response characteristics under various working conditions were studied. Taking the angular acceleration of the main reducer gear as the evaluation index of transient impact,the transient shock response characteristics of the transmission system with Declutch condition and Tip out condition were compared and analyzed. The results show that the dynamic decoupling between the engine and the transmission system will cause the transmission system to "oscillate". The corresponding relationship between the torsional characteristics of the torsional vibration damper and the transient impact of the transmission system under the tip out condition is studied by the control variable method. The results show that the stiffness of the first-stage of the clutch has more influence on the transient impact strength than stiffness of the second-stage,the transient impact of the transmission system is more obvious by adjusting the stiffness of the first-stage.